2020
DOI: 10.12659/ajcr.921657
|View full text |Cite
|
Sign up to set email alerts
|

Durable Response to Brentuximab Vedotin-Based Chemotherapy in Refractory Hodgkin Lymphoma with Central Nervous System (CNS) Involvement

Abstract: Rare disease Background: CNS involvement in Hodgkin lymphoma is rare. Despite various treatment options, median overall survival is only 13 months after diagnosis of CNS involvement in relapsed/refractory HL. Case Report: A 29-year-old woman with classical HL (mixed cellularity) in clinical stage IIB was treated with multilineage chemotherapy and radiotherapy without achieving a sustained complete remission. Systemic and CNS progression of HL occurred at the age of 32 years and the patient received 2 cycles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…BV alone was reported to be insufficient for controlling CNS lesions [ 11 ]. On the other hand, other case reports have reported that combination chemotherapies, including BV, may be effective against CNS lesions when CNS lesions disrupt the BBB [ 2 , 3 ]. Although our case suggests that PV-BR chemotherapy may not prevent CNS relapse, further studies are warranted to determine the efficacy of PV in combination with other cytotoxic agents for treating CNS relapse involving disruption of BBB in DLBCL patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BV alone was reported to be insufficient for controlling CNS lesions [ 11 ]. On the other hand, other case reports have reported that combination chemotherapies, including BV, may be effective against CNS lesions when CNS lesions disrupt the BBB [ 2 , 3 ]. Although our case suggests that PV-BR chemotherapy may not prevent CNS relapse, further studies are warranted to determine the efficacy of PV in combination with other cytotoxic agents for treating CNS relapse involving disruption of BBB in DLBCL patients.…”
Section: Discussionmentioning
confidence: 99%
“…PV comprises an antibody-drug conjugate that targets CD79b. Although BV was reported to be effective against CNS lesions in combination chemotherapies, the effect of PV on CNS lesions has not been elucidated [ 2 , 3 ]. Combination therapy with PV, bendamustine, and rituximab (PV-BR) has been reported to be effective at treating relapsed/refractory DLBCL [ 4 ].…”
Section: Introductionmentioning
confidence: 99%